PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KEDISIPLINAN PEGAWAI PADA KANTOR BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KOTA BIMA - Eka Erniati; Mulyadin (JUIMA : JURNAL ILMU MANAJEMEN, 2022)
This study aims to determine how and how much influence work motivation and work environment on employee discipline at the Regional Disaster Management Agency (BPBD) Bima City office. The population used is all employees of the Regional Disaster Management Agency (BPBD) Bima city, totaling 44 people (employees) with details of 30 ASN and 14 honorary people. The sample used in this study were 30 civil servants. Samples were taken by purposive sampling. Data collection methods are observation, interviews, literature studies and questionnaires. The analysis technique is multiple linear regression analysis using IBM SPSS 21 software. The results show that: (1) Work motivation partially affects employee discipline at the regional disaster management agency (BPBD) Bima city. (2) Work environment partially affects employee discipline. employee discipline at the regional disaster management agency (BPBD) office of Bima city. (3) Simultaneously or simultaneously work motivation and work environment affect employee discipline at the regional disaster management agency (BPBD) office of Bima city.